KARAKTERISTIK DAN PREFERENSI HABITAT KAKAKTUA SUMBA (Cacatua sulphurea citrinocristata) DI TAMAN NASIONAL LAIWANGI WANGGAMETI PROVINSI NUSA TENGGARA TIMUR - Oki Hidayat; Kayat Kayat (Widyariset, 2014)
Sumba cockatoo (Cacatua sulphurea citrinocristata) is an endangered endemic bird, which requires a serious attention. Sumba cockatoo is protected by Government Regulation No.7/1999 and the Ministry of Forestry Regula- tion No. 350//Kpts-11/1997. The aim of this study was to determine the characteristics and habitat preferences of Sumba cockatoo at Laiwangi Wanggameti National Park (LWNP) of East Nusa Tenggara Province. Vegetation analysis by making plots of 2 km in length with a total of 20 plots per location was used to discover the habitat characteristics. Chi-square test was used to determine the preference of cockatoo habitat variable. The habitat preference was analyzed by Neu’s method. The result showed that the habitat of Sumba cockatoo at LWNP has a relatively good richness of species with relatively even numbers each (good evenness). The habitat variables at LWNP were at altitude with the range of 251–400 meters above the sea level and the grade of slopeness was rather steep i.e. 26–40 % whereas the rampnesss is at 3–8 %. The most preferred location of Sumba cockatoo was at Billa forest block.